Evaluation of Sexually Transmitted Diseases in Sexual Assault and Abuse Cases - Çağlayan, Derya; Kaya, Ahsen; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2020)
It is important to evaluate sexual assault and sexual abuse cases in terms of sexually transmitted diseases (STD) as well as physical and psychological trauma. In these cases, the physical examination is generally limited to the determination of trauma findings and sample collection for identification of the assailant. Although there are many sexually transmitted infections such as Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Hepatitis B virus, Human immunodeficiency virus and syphilis, there is no standardized guideline for screening tests and prophylaxis practices in our country. Therefore, the risk of infection transmission should be considered in all cases and, if necessary, treatment and prophylaxis practices should be evaluated. In addition, in cases where the assailant can be reached, the examination of these persons should be performed in order to determine the need for medical care of the victim for STDs and to establish the causality and the judicial process of the assailant. In this review, it is aimed to draw attention of healthcare workers, with medicolegal aspects, to the subjects of the evaluation of sexually transmitted diseases in sexual assault and sexual abuse victims and examination of the assailant.
Keywords: forensic medicine; sexual assault; sexual abuse; sexually transmitted diseases